Asuhan Kebidanan Pada Ibu Pasca Persalinan Di PMB Riri Suyanti Wilayah Kerja Puskesmas XIII Koto Kampar Tahun 2022 - Fitri , Diva; Mayasari, Endang (Evidence Midwifery Journal, 2023)
Postpartum is a period where there are a series of changes in the mother that have an impact on the physical, psychological and social. To optimize the health of mothers and babies, postpartum care must be an ongoing process, with care and support tailored to the needs of each postpartum mother so that the care provided can help the mother through her postpartum period. Postpartum care consists of monitoring and examination. The examination materials included measuring the mother's body temperature and pulse, recording blood pressure, examining the breasts, assessing uterine involution, monitoring lochia. The purpose of this case is to find out the midwifery care given to Mrs. Y aged 31 years P1A0H1 which is experiencing good changes from day to day, 6 hours postpartum the mother complains of pain in the perineal wound area, and on the sixth day the mother does not feel pain anymore in the perineal area. suture area. From the results of this study, it is expected that the post-partum mother always maintains the cleanliness of the perineum that has been done well. Thus the care provided to these patients goes well.